Does Nursing Shift Influence Adherence to Central-Line Maintenance Bundles?. (October 2020) - Fox, Josephine; Russell, Robert; Grimes, Lydia; Gasama, Heather; Sona, Carrie; Wood, Helen; Warren, David
Abstract : Background: Proper care and maintenance of central lines is essential to prevent central-line–associated bloodstream infections (CLABSI). Our facility implemented a hospital-wide central-line maintenance bundle based on CLABSI prevention guidelines. The objective of this study was to determine whether maintenance bundle adherence was influenced by nursing shift or the day of week. Methods: A central-line maintenance bundle was implemented in April 2018 at a 1, 266-bed academic medical center. The maintenance bundle components included alcohol-impregnated disinfection caps on all ports and infusion tubing, infusion tubing dated, dressings, not damp or soiled, no oozing at insertion site greater than the size of a quarter, dressings occlusive with all edges intact, transparent dressing change recorded within 7 days, and no gauze dressings in place for >48 hours. To monitor bundle compliance, 4 non–unit-based nurse observers were trained to audit central lines. Observations were collected between August 2018 and October 2019. Observations were performed during all shifts and 7 days per week. Just-in-time feedback was provided for noncompliant central lines. Nursing shifts were defined as day (7:00 a.m. to 3:00 p.m.), evening (3:00 p.m. to 11:00 p.m.), and night (11:00 p.m. to 7:00 a.m.). Central-line bundle compliance between shifts were compared using multinomial logistic regression. Bundle compliance between week day and weekend were compared using Mantel-Haenszel 2 analysis. Results: Of the 25, 902 observations collected, 11, 135 (42.9%) were day-shift observations, 11, 559 (44.6%) occurred on evening shift, and 3, 208 (12.4%) occurred on the night shift. Overall, 22, 114 (85.9%) observations occurred on a week day versus 3, 788 (14.6%) on a Saturday or Sunday (median observations per day of the week, 2, 570; range, 1, 680–6, 800). In total, 4, 599 CLs (17.8%) were noncompliant with > 1 bundle component. The most common reasons for noncompliance were dressing not dated (n = 1, 577; 44.0%) and dressings not occlusive with all edges intact (n = 1340; 37.4%). The noncompliant rates for central-line observations by shift were 12.8% (1, 430 of 1, 1, 135) on day shift, 20.4% (2, 361 of 11, 559) on evening shift, and 25.2% (808 of 3, 208) on night shift. Compared to day shift, evening shift (OR, 1.74; 95% CI, 1.62–1.87; P < .001) and night shift (OR, 2.29; 95% CI, 2.07–2.52; P < .001) were more likely to have a noncompliant central lines. Compared to a weekday, observations on weekend days were more likely to find a noncompliant central line: 914 of 3, 788 (24.4%) weekend days versus 3, 685 of 22, 114 (16.7%) week days ( P < .001). Conclusions: Noncompliance with central-line maintenance bundle was more likely on evening and night shifts and during the weekends. Funding: None Disclosures: None